An Analysis of Second Grade of Elementary School Students' Ability in Learning Words Using Real Fruit Objects - Carolina, Carolina (Jurnal Basicedu, 2022)
The problem in this study is how effective the use of real objects from fruits is on students' ability to learn vocabulary. The purpose of this study was to determine whether the use of real objects was quite effective in students' ability to learn vocabulary. The population of this study was 192 students in grade 2 SD Brigjend Katamso2014/2015. The sample in this study was 42 students which consisted of 23 students, and 19 students. In this study, the method used in collecting data is by using qualitative and quantitative. In the qualitative method, the researcher uses observation during the learning process in the classroom. While in the quantitative method, the researcher uses questions in the form of a multiple-choice test. In this study, the media used in data collection was in the form of paper. The results showed that using real objects was quite effective in learning vocabulary. This research is based on the results of the students' abilities who achieved an average score of 89.4. 37 students get 80-100, and 5 students score 66-73. These results can be concluded that students can be categorized as capable. The use of real objects in teaching vocabulary makes students more enthusiastic and enjoys the teaching and learning process. Students are happy because they can taste fruits and can actively answer questions easily. So the teacher must be able to create a pleasant situation in the teaching and learning process.